The Universidade Federal da Fronteira Sul in the Brazilian scenario: notes from Darcy Ribeiro - Dionei Ruã dos Santos; Sidinei Pithan da Silva; Maria Cristina Pansera de Araujo (Universidade Federal do Norte do Tocantins, 2020)
The article analyzes the founding ideals of universities directly influenced by Darcy Ribeiro as well as his books and texts, aiming to diagnose their presence in universities today. The text establishes some possible relations with the project of the Universidade Federal da Fronteira Sul and the Interdisciplinary course in Rural Education, pointing out possible marks of this author, at the same time rescuing his concepts and updating them due to unprecedented fields of possibilities, especially in the which refers to the entry and permanence, in Higher Education, of peoples historically excluded from society, as is the case of indigenous and rural subjects.